Switched Reluctance Motor and its Utilization in Traction Applications - Rafajdus, Pavol; Hrabovcova, Valeria; Janousek, Ladislav; Hudak, Peter (Communications - Scientific letters of the University of Zilina, 2001)
This paper deals with the performances of switched reluctance motor (SRM) and with its utilization in electric traction. The investigation of SRM equivalent circuit parameters by measurement and by finite element method is described. The calculated and measured values of parameters are used in the mathematical model of SRM, which was simulated. The simulation outputs are time profiles of the phase currents, voltages and torque and also the torque/speed characteristic, which can be used for the traction characteristic calculation. The dependencies of the losses and efficiency on the speed are shown. The comparison of performances of induction machine and SRM is shown at the end.